(untitled) (Nordic Journal of African Studies, 1996)
This paper is about the contribution of women to the moral health and uprightness of African society. It begins with a discussion of the role of women as moral teachers in African families and underscores the centrality of women in the moral upbringing of children. As part of their traditional care-giving roles, African women have been in a unique and strategic position not only to produce and sustain life but also to instill socio-religious values and moral standards in the family and society. This moral education includes teaching children personal discipline, how to uphold sexual morality, what is expected of them at various stages of their lives as well as the moral requirements of chastity, marital fidelity and family responsibilities for men, women and children. The discussion next turns to an explanation of the role of women in religion and takes up the twin issues of the role and position of women in African Christian churches and their contribution to community worship life. It is argued that through their healing ministry and pastoral infrastructure, a great number of women in Africa play a key role in bringing love to the continent and a sense of hope and optimism to those who live in despair. This role is closely linked to their involvement in various peace processes and efforts at conflict resolution in and outside Africa, particularly in strife-torn regions of the continent. The author presents some of the subtle and explicit ways in which the dominant male ideology has consistently used female sexuality to reinforce female subordination and devalue women’s moral role in African society. The last part of the paper deals with the issues of moral delocalization, social change and modernization in Africa, and how these processes have re-defined the role of women and the overall moral character of African societies. The conclusion stresses that both the empowerment of women and re-assessment of traditional family values and moral standards must be addressed if the moral health of African societies is to be improved.